Kerangka Praktik Kenegaraan dalam Narasi Apriori Pembangunan Berkelanjutan sebagai Hak Konstitusional: Sentralisasi Pendekatan Ekosentris dalam Melawan Kenisbian Utilitas Pendekatan Antroposentris - Ifdal, Abdurrahman Al-Fatih (Jurnal Konstitusi & Demokrasi, 2022)
Sustainable development is a colossal narrative of state elites to institutionalize the right to development which, instead of being oriented towards harmonization of development efforts with efforts to protect the environment, is actually based on human interests. The inherent causality of this effort has an impact on systemic environmental damage in various countries. When the environment is no longer able to recover itself according to the timeline of meeting the needs of human civilization, an ambitious approach such as ecocentrism needs to be used as a counter-narrative to the anthropocentrism approach which tends to be relative: it looks useful, but in fact it is not. This study argues that sustainable development no longer shows its relevance when the earth's situation has entered a crisis stage: the environment is no longer able to keep up with the destructive demands of human fulfillment and continues to increase at an accelerating pace. Furthermore, the focus of this research is thus to question the relevance of sustainable development which was sparked by an a priori narrative, namely a narrative centered on the presupposition that environmental protection is aimed at fulfilling the interests of the development of human civilization. In the condition of the earth that has experienced the current crisis, setting standards that are higher than the status quo for mitigating and adapting to climate change may still be lacking in preventing crises on earth. Reflecting on the above, this research seeks to offer a new paradigm in transforming an ecocentric approach by reflecting on state practices that are recognized at the international level. With this paradigm transformation, the anthropocentric approach can be overhauled in order to accommodate the current earth crisis situation.